2021
DOI: 10.3390/v13020239
|View full text |Cite
|
Sign up to set email alerts
|

The Role of ND10 Nuclear Bodies in Herpesvirus Infection: A Frenemy for the Virus?

Abstract: Nuclear domains 10 (ND10), a.k.a. promyelocytic leukemia nuclear bodies (PML-NBs), are membraneless subnuclear domains that are highly dynamic in their protein composition in response to cellular cues. They are known to be involved in many key cellular processes including DNA damage response, transcription regulation, apoptosis, oncogenesis, and antiviral defenses. The diversity and dynamics of ND10 residents enable them to play seemingly opposite roles under different physiological conditions. Although the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 183 publications
(175 reference statements)
0
5
0
Order By: Relevance
“…The loss of the ICP0 N-terminus showed a moderate reduction of viral yield and a delayed expression of the true late protein gC, indicating a role of the ICP0 N-terminus in HSV-1 infection. ND10 has been reported to have both positive and negative effects on HSV-1 and other herpes infections [ 27 , 52 ]. It remains unclear whether the differential PML ubiquitination catalyzed by ICP0 affects the interaction between ICP0 and other ND10 components besides dispersing the ND10 structure and, more importantly, whether there are ND10 components differentially ubiquitinated by ICP0 but which are not degraded via proteasomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of the ICP0 N-terminus showed a moderate reduction of viral yield and a delayed expression of the true late protein gC, indicating a role of the ICP0 N-terminus in HSV-1 infection. ND10 has been reported to have both positive and negative effects on HSV-1 and other herpes infections [ 27 , 52 ]. It remains unclear whether the differential PML ubiquitination catalyzed by ICP0 affects the interaction between ICP0 and other ND10 components besides dispersing the ND10 structure and, more importantly, whether there are ND10 components differentially ubiquitinated by ICP0 but which are not degraded via proteasomes.…”
Section: Discussionmentioning
confidence: 99%
“…Upon HSV-1 entry, ND10 components converge to the incoming DNA to restrict viral expression [ 7 , 24 , 25 ]. ICP0 E3-mediated PML and Sp100 degradation help to disperse ND10 components and thereby release the DNA repression imposed by ND10 [ 26 , 27 ]. The siRNA knockdown of PML and Sp100 enhances the growth of HSV-1 in the absence of ICP0 [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, several studies have indicated that some PML NB components can be advantageous for herpesvirus infection and the establishment of latent infection. These observations suggest that PML NBs may play both pro-viral and antiviral roles, reviewed in [ 98 ].…”
Section: The Structure Composition and Function Of Pml Nbsmentioning
confidence: 99%
“…Viruses may trigger the degradation of heterochromatin components, such as Smc5/6, which is targeted by HBV, or components of PML bodies, which provide a favorable environment for heterochromatin formation (139,140). This can, for example, be PML itself or SP100, which are targeted by HSV-1 (141), or ATRX/DAXX, targeted by adenovirus (139).…”
Section: Viruses Drive Global Genome Opening By Switching or Tuning S...mentioning
confidence: 99%